A multiple‐site field study of stabilized hydrogen peroxide for drinking water disinfection. Issue 4 (7th August 2019) - Vadasarukkai, Yamuna S.; Guo, Xinhai (August); Tyssen, Robert; Hares, Joanna El; Feyen, Ludo; Liss, Steven N.; Shubat, Jim; Abernethy, Robert
Abstract: This study examined the impact of changing the secondary disinfectant from chlorine to a stabilized hydrogen peroxide (SHP) in three full‐scale drinking water treatment plants serving small communities in the provinces of Ontario and Newfoundland, Canada. In all three communities, the SHP residuals were maintained within the limits specified by local regulators, with the exception of one of the sites in Newfoundland, where residuals were outside these limits on several occasions during the study. Following the transition to the SHP system, total coliforms and Escherichia coli consistently tested negative (nondetected) in all cases. Switching to the SHP system reduced concentrations of total trihalomethanes to 22–44 μg/L and total haloacetic acids to 47–70 μg/L, corresponding to 72 ± 9 and 67 ± 11% reductions, respectively. The present study indicated that changing the secondary disinfectant to SHP did not negatively affect the polyvinyl chloride and ductileiron pipes in the distribution systems studied.